Radial Glia in Echinoderms - Mashanov, Vladimir (Dev Neurobiol, 2018)
Radial glial cells are crucial in vertebrate neural development and regeneration. It has been recently proposed that this neurogenic cell type might be older than the chordate lineage itself and might have been present in the last common deuterostome ancestor. Here, we summarize the results of recent studies on radial glia in echinoderms, a highly regenerative phylum of marine invertebrates with shared ancestry to chordates. We discuss the involvement of these cells in both homeostatic neurogenesis and post-traumatic neural regeneration, compare the features of radial glia in echinoderms and chordates to each other, and review the molecular mechanisms that control differentiation and plasticity of the echinoderm radial glia. Overall, studies on echinoderm radial glia provide a unique opportunity to understand the fundamental biology of this cell type from evolutionary and comparative perspectives.